#TITLE_ALTERNATIVE# - (NIM 10205048), AGUSTINA
An analytical expression for evaluating the transmission coefficient and tunnel current of an electron in metal-oxide-semiconductor hetero junction anisotropic material has been derived. The Si(100)/SiO2/Si(100) heterostructure was used to examine the analytic expression. Airy function numerical method is chosen in calculating the solution of Schrodinger equation for trapezoidal barrier. The transmission coefficient is calculated for electron energy 0.1 eV to 4 eV. The transmission coefficient is superior as the energy of electron higher than 3 eV. By varying the applied bias voltage to the potential barrier, barrier width, electron incident angle, and electron velocity, the different value of transmission coefficient be obtained. The electron effective mass in the oxide layer, electron velocity, and the Fermi energy are three fitting parameters. It is shown that the calculated tunnel current is well fitted to the measured one in low applied bias voltage.